The 1975 Referendum - Butler, David. author. aut Link
XIII, 315 p.
Keywords: The holding of referendums has returned to the British political agenda. The re-issue of the story of what happened in the country's only nationwide referendum so far is therefore timely. This book tells the full story of the politics, high and low, as well as the innovative campaigning and administration involved in a key event in United Kingdom history.